Research and application of real-time monitoring and early warning thresholds for multi-temporal agricultural products information - Shi-wei XU; Yu WANG; Sheng-wei WANG; Jian-zheng LI (Journal of Integrative Agriculture)
Monitoring and early warning is an important means to effectively prevent risks in agricultural production, consumption and price. In particular, with the change of modes of national administration against the background of big data, improving the capacity to monitor agricultural products is of great significance for macroeconomic decision-making. Agricultural product information early warning thresholds are the core of agricultural product monitoring and early warning. How to appropriately determine the early warning thresholds of multi-temporal agricultural product information is a key question to realize real-time and dynamic monitoring and early warning. Based on the theory of abnormal fluctuation of agricultural product information and the research of substantive impact on the society, this paper comprehensively discussed the methods to determine the thresholds of agricultural product information fluctuation in different time dimensions. Based on the data of the National Bureau of Statistics of China (NBSC) and survey data, this paper used a variety of statistical methods to determine the early warning thresholds of the production, consumption and prices of agricultural products. Combined with Delphi expert judgment correction method, it finally determined the early warning thresholds of agricultural product information in multiple time, and carried out early warning analysis on the fluctuation of agricultural product monitoring information in 2018. The results show that: (1) the daily, weekly and monthly monitoring and early warning thresholds of agricultural products play an important early warning role in monitoring abnormal fluctuations with agricultural products; (2) the multi-temporal monitoring and early warning thresholds of agricultural product information identified by the research institute can provide effective early warning on current abnormal fluctuation of agricultural product information, provide a benchmarking standard for China's agricultural production, consumption and price monitoring and early warning at the national macro level, and further improve the application of China's agricultural product monitoring and early warning.